Java Image Processing Recipes With OpenCV and JVM - Modrzyk, Nicolas (Apress, 2018)
Quickly obtain solutions to common Java image processing problems, learn best practices, and understand everything OpenCV has to offer for image processing. You will work with a JVM image wrapper to make it very easy to run image transformation through pipelines and obtain instant visual feedback. This book makes heavy use of the Gorilla environment where code can be executed directly in the browser, and image transformation results can also be visualized directly in the browser. Java Image Processing Recipes includes recipes on more advanced image manipulation techniques, such as image smoothing, cartooning, sketching, and mastering masks to apply changes only to parts of the image. You'll see how OpenCV features provide instant solutions to problems such as edges detection and shape finding. Finally, the book contains practical recipes dealing with webcams and various video streams, giving you ready-made code with which to do real-time video analysis. You will: Create your personal real-time image manipulation environment Manipulate image characteristics with OpenCV Work with the Origami image wrapper Apply manipulations to webcams and video streams.